MANAGEMENT DECISION OF JACKS FORM OF IMPLEMENTATION OF ORGANIZATIONAL FUNCTION OF PUBLIC ADMINISTRATION - VAHANOVA, LYUDMYLA; YURYCHYNA, IRYNA; KARPANASYUK, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Today, forms of management are external, constantly and typically fixed manifestations of practical activity of public authorities or local governments in the formation and implementation of management goals and functions and ensuring their own lives. They give an idea of what and how is done in these bodies to exercise their competence.Legal forms of management activities record management decisions and actions that have legal content (establishment and application of legal norms). They are used in the preparation, adoption and implementation of management decisions. To ensure the effectiveness of management, it is important that the main actions, operations, forecasts, expertise, statistical generalizations, information, sociological data on which a management decision is based, are clearly documented, ie presented in the appropriate legal form. In most cases, management decisions are a legal act, correlated with the competence of the body, as well as with the current substantive and procedural legal norms. The role of a legal act in public administration is determined by the extent to which all legal procedures and requirements have been complied with during its preparation and adoption and what real administrative potential it has.The article is devoted to deepening the theoretical foundations and developing practical recommendations for management decisions. To this end, the theoretical foundations and features of management decisions are considered, and specific recommendations for the effectiveness of management decisions are provided.The essence of the managerial decision on several aspects is investigated. The content of the organizational function of the state as the main component of the management decision is characterized.The basic requirements for making managerial decisions are offered. It is recommended to formulate the decision clearly and concisely together with specific tasks, actions for the implementation of the decision and should indicate: specific ways and means of action; deadlines, composition of performers responsible for their implementation; the order of interaction of performers; necessary resources; forms of control and accounting of intermediate and final results; list and content of documents that reflect the progress of the decision.
Keywords: management decision; organizational function; state; public administration